Degradation of zearalenone and aflatoxin B1 by Lac2 from Pleurotus pulmonarius in the presence of mediators. (15th October 2021) - Song, Yanyi; Wang, Yanan; Guo, Yongpeng; Qiao, Yingying; Ma, Qiugang; Ji, Cheng; Zhao, Lihong
Abstract: The contamination of foods and feeds with mycotoxins has been an issue of global significance. For mycotoxin detoxification, enzymatic biodegradation using laccase has received much attention. In this study, a laccase gene lac2 from the fungus Pleurotus pulmonarius was expressed in the Pichia pastoris X33 yeast strain to produce recombinant proteins. Enzymatic properties of recombinant Lac2 and its ability to degrade zearalenone (ZEN) and Aflatoxin B1 (AFB1) in the presence of four mediators (ABTS, TEMPO, AS and SA) were investigated. Result showed that the optimum pH and temperature of recombinant Lac2 were 3.5 and 55 °C, respectively. Lac2 was not sensitive to heat and stable under both acidic and alkaline conditions. Lac2-ABTS and Lac2-AS were efficient systems for ZEN degradation over a wide range of pH (4–8) and temperature (40–60 °C). Lac2-AS was the most efficient system for AFB1 degradation, reaching 99.82% of degradation at pH 7 and 37 °C after 1 h of incubation. Finally, the Lac2-mediator oxidation products were structurally characterized. This study lays a solid foundation for the application of Lac2 laccase combined with AS for degrading mycotoxin in food and feed. Highlights: Our study provides useful information for the Pleurotus pulmonarius laccase2. The use of mediators enhances the mycotoxins degradation ability of laccase2. The laccase-mediator oxidation products were structurally characterized. The laccase-mediator reaction mechanisms were discussed.